Defining the Protein Phosphatase 2A (PP2A) Subcomplexes That Regulate FoxO Transcription Factor Localization - Adeline M. Luperchio; Daniel J. Salamango (Cells)
The family of forkhead box O (FoxO) transcription factors regulate cellular processes involved in glucose metabolism, stress resistance, DNA damage repair, and tumor suppression. FoxO transactivation activity is tightly regulated by a complex network of signaling pathways and post-translational modifications. While it has been well established that phosphorylation promotes FoxO cytoplasmic retention and inactivation, the mechanism underlying dephosphorylation and nuclear translocation is less clear. Here, we investigate the role of protein phosphatase 2A (PP2A) in regulating this process. We demonstrate that PP2A and AMP-activated protein kinase (AMPK) combine to regulate nuclear translocation of multiple FoxO family members following inhibition of metabolic signaling or induction of oxidative stress. Moreover, chemical inhibitor studies indicate that nuclear accumulation of FoxO proteins occurs through inhibition of nuclear export as opposed to promoting nuclear import as previously speculated. Functional, genetic, and biochemical studies combine to identify the PP2A complexes that regulate FoxO nuclear translocation, and the binding motif required. Mutating the FoxO-PP2A interface to enhance or diminish PP2A binding alters nuclear translocation kinetics accordingly. Together, these studies shed light on the molecular mechanisms regulating FoxO nuclear translocation and provide insights into how FoxO regulation is integrated with metabolic and stress-related stimuli.